2011
DOI: 10.1007/s11999-011-1801-6
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of an Ossific Nucleus Does Not Protect Against Osteonecrosis After Treatment of Developmental Dysplasia of the Hip

Abstract: Background Osteonecrosis (ON) is a major complication after treatment of developmental dysplasia of the hip (DDH). Several studies have explored the absence of the femoral head ossific nucleus at the time of hip reduction as a risk factor for the development of ON, but findings have been inconsistent. Questions/purposes We therefore determined the incidence of ON in children who underwent reduction of a dislocated hip in the presence or absence of the ossific nucleus. Patients and MethodsWe retrospectively rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 10 publications
2
39
1
Order By: Relevance
“…We found no difference in abduction angle with the numbers available in either those who developed AVN or those displaying abnormal enhancement on pMRI. Consistent with prior studies, gender [3], laterality [3], previous treatment with a Pavlik harness/abduction brace [3,18,24], and concurrent procedure [18] all had no effect on final AVN rates with the numbers available in our cohort. The presence or absence of the ossific nucleus at the time of reduction remains a controversial issue.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We found no difference in abduction angle with the numbers available in either those who developed AVN or those displaying abnormal enhancement on pMRI. Consistent with prior studies, gender [3], laterality [3], previous treatment with a Pavlik harness/abduction brace [3,18,24], and concurrent procedure [18] all had no effect on final AVN rates with the numbers available in our cohort. The presence or absence of the ossific nucleus at the time of reduction remains a controversial issue.…”
Section: Discussionsupporting
confidence: 86%
“…In their review of the literature, Cooper et al [8] found a wide range in reported AVN rates between 3% and 60%, which they attributed to variations in the definition of AVN and the length of followup. In a more recent sample [4,6,7,16,19,21,24,30,34], AVN rates varied more consistently between 7% and 36%, but again a wide variety of radiographic criteria was used to identify AVN. In this study, we used Salter criteria as did Tiderius et al [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies proposing delaying the treatment of DDH hypothesized that the development of the microcirculation in the femoral head, concomitant with the radiographic appearance of the ossific nucleus, would protect against osteonecrosis [16,75]. However, other studies [21,53,70] did not find older age and the presence of ossific nucleus as protective factors for osteonecrosis. Those opposing delaying treatment would further ague that it could potentially compromise acetabular remodeling, whereas early reduction may prompt better development of a congruent hip [22].…”
Section: Discussionmentioning
confidence: 96%
“…We realized in previous studies [12][13][14]16] that classifying hips as described by Bucholz and Ogden [1] can be challenging and confusing with questionable reliability. Reliability, or reproducibility, is a prerequisite of any scientific measure.…”
Section: Introductionmentioning
confidence: 99%